The Influence of Live Streaming, Customer Reviews, and Brand Image on Purchasing Decisions of Compass Shoes on Shopee E-Commerce Platform - Fahren Heigy Ferdinansyah; Muttaqien, Zaenul; Murdiyanto, Edi (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the influence of live streaming, customer reviews, and brand image on purchasing decisions for Compass shoes on Shopee. Using a quantitative causal-associative approach, data were collected from 96 respondents through Likert-scale questionnaires and analyzed using SEM-PLS with SmartPLS 4.0. The results show that brand image has a positive and significant effect on purchasing decisions, while live streaming and customer reviews have no significant partial effects. Thus, purchasing decisions are mainly influenced by brand perception rather than digital interaction features or online reviews. Keywords: Live Streaming; Purchase Reviews; Brand Image; Purchase Decision; E-Commerce